Pengembangan Kegiatan Ekstrakurikuler Dalam Meningkatkan Bakat Kaligrafi Siswa Di Madrasah Aliyah Swasta 12 Perbaungan - Neliwati Neliwati; Mardhiah Putri Jerohmi; Suci Apriani; Nur Awaliyah Afrinda Sari (Journal on Education, 2024)
Calligraphy or khat is a science that introduces hijaiyah letters, after which they are combined with examples of verses from the Koran and assembled into very beautiful writing. The results of this research are to develop calligraphy extracurricular activities in improving students' talents at MAS Al-Washliyah 12 Perbaungan, so teachers need to do several things, namely preparing calligraphy lessons, using methods that make it easier for students, motivating students to be more enthusiastic in learning calligraphy, and evaluating writing that has been studied so that it is more in line with the rules of calligraphy. The research method used is qualitative research and a case study at MAS Al-Wahliyah 12 Perbaungan.